2019
DOI: 10.1111/jace.16295
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles study, fabrication, and characterization of (Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C high‐entropy ceramic

Abstract: The formation possibility of (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )C high-entropy ceramic (HHC-1) was first analyzed by the first-principles calculations, and then, it was successfully fabricated by hot-pressing sintering technique at 2073 K under a pressure of 30 MPa. The first-principles calculation results showed that the mixing enthalpy and mixing entropy of HHC-1 were −0.869 ± 0.290 kJ/mol and 0.805R, respectively. The experimental results showed that the as-prepared HHC-1 not only had an interesting singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 260 publications
(68 citation statements)
references
References 46 publications
(34 reference statements)
6
49
0
1
Order By: Relevance
“…However, the HEC had a theoretical density of only 93%, which would have resulted in a relatively low Vicker's hardness. Sarker P et al 20 synthesised several ve transition metal containing carbides and found a general increase in the nanoindentation elastic modulus and hardness compared to the monocarbides, comparable to that reported by Csanadi et al 70 Ye et al 57 have reported a very high nanoindentation hardness for (Ti,Zr,Hf,Nb,Ta)C of 40.6 GPa, and also an indentation elastic modulus higher than the rule of mixture value for the monocarbides obtained from the literature. They also found the indentation fracture behaviour and properties to be similar to those of the monocarbides reported in the literature.…”
Section: Mechanical Propertiessupporting
confidence: 73%
See 1 more Smart Citation
“…However, the HEC had a theoretical density of only 93%, which would have resulted in a relatively low Vicker's hardness. Sarker P et al 20 synthesised several ve transition metal containing carbides and found a general increase in the nanoindentation elastic modulus and hardness compared to the monocarbides, comparable to that reported by Csanadi et al 70 Ye et al 57 have reported a very high nanoindentation hardness for (Ti,Zr,Hf,Nb,Ta)C of 40.6 GPa, and also an indentation elastic modulus higher than the rule of mixture value for the monocarbides obtained from the literature. They also found the indentation fracture behaviour and properties to be similar to those of the monocarbides reported in the literature.…”
Section: Mechanical Propertiessupporting
confidence: 73%
“…Ye et al built 100 supercells for rock salt (Hf 0.2 Zr 0.2 Ta 0.2 -Nb 0.2 Ti 0.2 )C. 57 Each supercell contained 64 atoms with a random distribution of the metal atoms, and the cation stoichiometry was nearly equimolar. These supercells were then fully relaxed using DFT calculations to give total energies and atomic positions.…”
Section: General Structure Featuresmentioning
confidence: 99%
“…HECs were successfully fabricated in the form of coatings some years ago, [3] but have only recently been reported in bulk form. [4] Due to the emerging fundamental interest and potential applications, several compositions have been fabricated, [5][6][7][8][9] and properties such as hardness and oxidation behavior [10,11] have been investigated. These compositions mainly contain refractory transition metal elements, and there is a vast potential compositional space still to explore, where compositions with advantageous properties are likely to exist.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, modeling has revealed the importance of size and interatomic force constant disorder resulting in thermally-insulative HECs [78,[108][109][110]. Various other modeling studies have been conducted [60,[111][112][113][114][115]. A complete review and critical assessment of the modeling of HECs is beyond the scope of this perspective article.…”
Section: Modelingmentioning
confidence: 99%